2020
DOI: 10.1136/openhrt-2019-001233
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging prior to transcatheter aortic valve implantation in the UK

Abstract: ObjectiveThis cross-sectional observational study sought to describe variations in CT in the context of transcatheter aortic valve implantation (CT-TAVI) as currently performed in the UK.Methods408 members of the British Society of Cardiovascular Imaging were invited to complete a 27-item online CT-TAVI survey.Results47 responses (12% response rate) were received from 40 cardiac centres, 23 (58%) of which performed TAVI on-site (TAVI centres). Only six respondents (13%) performed high-volume activity (>200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In our CT protocol, radiation exposure was already quite low with a median DLP of 410.5 mGy·cm. A cross-sectional observational study in the UK published in 2020 reported a median DLP of 675 mGy·cm for CT studies prior to TAVI ( 25 ). Considering that most TAVI candidates are multimorbid septuagenarians or octogenarians (median age was 80 years in our cohort), further reductions in radiation exposure in this population are unlikely to be of any benefit for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our CT protocol, radiation exposure was already quite low with a median DLP of 410.5 mGy·cm. A cross-sectional observational study in the UK published in 2020 reported a median DLP of 675 mGy·cm for CT studies prior to TAVI ( 25 ). Considering that most TAVI candidates are multimorbid septuagenarians or octogenarians (median age was 80 years in our cohort), further reductions in radiation exposure in this population are unlikely to be of any benefit for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Schicchi et al 4 and Kok et al 8 used DSCT with a single prospective ECG-triggered acquisition and DSCT, with a retrospective ECG-triggered acquisition and a shorter scanning length. The study by Harries et al 5 collected protocols from many institutes, consisting of many types of scanners and techniques. The report showed a wide range of effective radiation doses in CT-pre TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary planning based on multidimensional imaging is key to achieve favorable outcomes during the procedure as well as subsequently, with multidetector contrast-enhanced computed tomography (CT) playing a central role 6 9 . The benefits of CT include accurate appraisal of vessel dimensions, angles and calcifications, suitable for decision-making in terms of procedural details as well as TAVI device type and size, on top of overall risk assessment and prediction of complications such as permanent pacemaker implantation or prosthesis-patient mismatch 10 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of CT include accurate appraisal of vessel dimensions, angles and calcifications, suitable for decision-making in terms of procedural details as well as TAVI device type and size, on top of overall risk assessment and prediction of complications such as permanent pacemaker implantation or prosthesis-patient mismatch 10 18 . However, CT exams may provide a confounding and overwhelming plethora of parameters and measurements, limiting the eventual informativeness of a CT report, leading to inappropriate decisions and strategies, with several apparently useful features actually proving of limited predictive accuracy 9 , 19 .…”
Section: Introductionmentioning
confidence: 99%